Ultrasonographic imaging of early fetal development in Black-Bengal goats - KUMAR, JITENDRA; CHANDOLIA, R K; VERMA, S K (The Indian Journal of Animal Reproduction, 2005)
B-mode real-time ultrasonography of five Black-Bengal goats was undertaken to assess serial development of kids in utero. The scanning at various stages of gestation revealed various features of development of kids. Fetus changed its shape from Cshape to oblong. The amnion appeared as dotted echoic membrane. Amnion appeared to make a sac like formation enclosing fluid inside. The full fetal iniages were obtained on day 46, while cotyledons on day 53. The resting on neck on back on day 63 was another important observation. On day 63 full view of placentornes was also observed. Opening of mouth and taking of fetal fluid inside was also observed duriQg this study . . The study will help the practitioners or sonographers to differentiate normal and abnormal development of early kids in utero in this species.